Pembuatan Website Sebagai Media Promosi Terpercaya SD Muhammadiyah 1 Padas - Anwar, Rosyida Nurul; Husna, Anis Risalatul; Nurjanah, Anggi; Setyars, Nugrahani Kartika; Winggasari, Mareta; Rahmasiwi, Dwinda Susi (Jurnal Pendidikan Tambusai, 2021)
The development of information technology in education began to show significant changes—the website's presence as a medium for disseminating relevant and efficient information today. The school website is a site that provides details of school implementation over time to build a progress narrative and convey success in school performance. This community service activity aims to assist schools in sharing information and giving a good impression and school professionalism to the broader community. The partner in this activity is Muhammadiyah 1 Padas Elementary School. The implementation method identifies partner problems in technology adaptation, finding solutions to partner problems, problem-solving, mentoring and evaluation. The website contains various things about schools, namely school profiles, the history of the school's establishment, profiles of educators and education staff, school activities, announcements, and contact persons. Having a school website has supported the realization of a Global Indonesia in terms of education.